An exploratory study on the selection process for promotional strategies of small-scale interior design companies - Manso, Kim Sarah C.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT This study determined how small-scale interior design companies selected the promotional strategies that would help them market their services to their target market. Through purposive sampling, nine (9) small-scale interior design companies were chosen. Participants were selected under the criteria that they are an independent small-scale company, which is defined by the MSMED Council (2011-2016) to have one to ninety-nine employees. Each company was represented by the owner-manager of the company. A qualitative research design using a survey questionnaire and an in-depth interview were utilized to obtain data regarding the companies' selection process for promotional strategies. The data-gathered were presented in figures and thematic tables. Similar themes were then identified and analyzed according to the objectives of the study. The findings of the study showed that the size of the company affected the selection and management of small-scale interior design companies. Limited resources caused small-scale companies consider the cost, the reach, the convenience, and the promotional strategy's alignment to the image of the company. The responsibility of the selection and management of promotions was often given to the owner-manager/s of the company. It was also found out that small-scale interior design companies very particular to the image and identity of the company, thus often hires graphic designers/specialists to make and develop promotional materials for the company. Majority of the companies identified that among all promotional strategies, they regard internet marketing as the most frequently used and the most effective promotional strategy in terms of reaching and gaining clients.
Thesis(BS Interrior Design)--University of the Philippines Diliman.
Keywords: Interior decoration firms -- Philippines; Interior decoration firms -- Marketing -- Philippines